"I know it's sensitive": Internet censorship, recoding, and the sensitive word culture in China. (February 2023) - Ye, WeiMing; Zhao, Luming
Abstract: This article conceptualizes the Sensitive Word Culture as a new theoretical lens for understanding how Chinese netizens interact with Internet censorship systems. Through the use of 22 in-depth interviews of Chinese Weibo users and netnography as empirical material, eight types of word recoding practices are identified and mapped into two discourse strategies, namely "evading detection" and "expanding interpretability." Drawing on the concepts of everyday resistance and everyday politics, we analyze the power relations behind these discourse strategies, and also identify the apolitical aspects and scope of the Sensitive Word Culture. One notable finding is that the Sensitive Word Culture is becoming a part of China's digital cultural production, influencing the development of slang and memes. This research offers insights into how censorship from artificial intelligence and human intelligence influences the online discourses on Chinese social media.